PENGARUH KEBIJAKAN DIVIDEN, PERPUTARAN TOTAL AKTIVA, DAN LABA PER LEMBAR SAHAM TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2019 - Thaufik Hidayat; Linna Ismawati (Manis: Jurnal Manajemen dan Bisnis, 2021)
Study aims to determine effect Dividend Policy, Total Assets Turnover, and Earning per Share on Stock Price. Research data obtained from annual financial reports. Quantitative research methods with path analysis. Withdrawal of samples using pooled data. The results of hypothesis can be obtained Total Assets Turnover hasn’t significant affect on Dividend Policy, Total Asset Turnover hasn’t significant affect on Earning per Share, Earning per Share has no significant on Dividend Policy. Dividend Policy, Total Asset Turnover and Earning Per Share partially and simultant has an affect on Stock Price.